Nutritional strategies for post-exercise recovery: a review - Pritchett, KL; Pritchett, RC; Bishop, P (South African Journal of Sports Medicine, 2011)
Finding the optimal nutrition regimen for enhanced recovery is fundamental in enhancing exercise training and performance. Therefore, research has aimed to examine post-exercise nutritional strategies for optimal recovery. Because muscle glycogen is the primary substrate utilised during high-intensity exercise, it must be replenished. Recent research has examined the effectiveness on recovery of adding protein to a post-exercise carbohydrate beverage. This review summarises and analyses the literature on nutritional strategies aimed at enhancing various indicators of post-exercise recovery: glycogen resynthesis, muscle damage and performance. Furthermore, the literature on Medline and Pubmed comparing the effectiveness of carbohydrate-only (CHO) beverage with a carbohydrate:protein (CHO:PRO) beverage on maximising recovery was reviewed. The methods and results of studies regarding post-exercise nutritional strategies for recovery were analysed. primary results of this review suggest that the optimal timing in regard to post-exercise nutritional strategies for maximal glycogen resynthesis is within the first 30 minutes after exercise. The literature suggests that 1.0 - 1.5 g.kg-1h-1 of carbohydrate ingested at 2-hour intervals after exercise for up to 6 hours may be optimal for recovery. The addition of protein to a post-exercise meal may supply additional amino acids necessary for muscle repair creating an anabolic condition.